2003
DOI: 10.1104/pp.103.027797
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Aquaporins Are Involved in Winter Embolism Recovery in Walnut Tree

Abstract: In perennial plants, freeze-thaw cycles during the winter months can induce the formation of air bubbles in xylem vessels, leading to changes in their hydraulic conductivity. Refilling of embolized xylem vessels requires an osmotic force that is created by the accumulation of soluble sugars in the vessels. Low water potential leads to water movement from the parenchyma cells into the xylem vessels. The water flux gives rise to a positive pressure essential for the recovery of xylem hydraulic conductivity. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(118 citation statements)
references
References 45 publications
6
110
0
2
Order By: Relevance
“…Though the local exchange of sugars may occur between the vessels and parenchyma cells in stem (Sauter et al 1973), the source of xylem sap glucose was not well identified. The accumulation of free sugars in the xylem sap may promote water movement into xylem vessels to refill embolized xylem by decreasing osmotic potential (Améglio et al 2001, Sakr et al 2003.…”
Section: Resultsmentioning
confidence: 99%
“…Though the local exchange of sugars may occur between the vessels and parenchyma cells in stem (Sauter et al 1973), the source of xylem sap glucose was not well identified. The accumulation of free sugars in the xylem sap may promote water movement into xylem vessels to refill embolized xylem by decreasing osmotic potential (Améglio et al 2001, Sakr et al 2003.…”
Section: Resultsmentioning
confidence: 99%
“…A tree was assumed to be dead when all its vegetative buds had dried deficiency because winter embolism is related to xylem osmolarity, i.e. to the concentrations in soluble C and N compounds Sakr et al 2003;Charrier and Ameglio 2011;Galvez et al 2013). Despite the fact that peach wood porosity is diffuse, positive xylem pressure plays only a minor role in recovery from winter embolism (Ameglio et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of aquaporins in the beginning of 1990's popularized the concept of membrane water channels (Connolly et al, 1998;Engel et al, 2000;Preston & Agre, 1991), and their roles were studied on membrane permeability (Johansson et al, 2000;Maurel, 2007;Sakr et al, 2003;Sarda et al, 1999;Van der Weerd et al, 2002). The most immediate decrease in ADC under dormancy inducing conditions occurred in the axillary buds of poplar followed by the vascular bud trace region (de Fay et al, 2000).…”
Section: Water Status Determined By Mri Techniques In Buds During Dormentioning
confidence: 99%